Body image concerns and weight control behaviors among medical students in Oman - Chhaya Akshay Divecha; Miriam Archana Simon (Wolters Kluwer Medknow Publications, 2022)
Background: Body image perceptions and satisfaction are known to influence health behaviors; however, data on body image concerns in medical students, especially in the Middle East, are scarce, with no studies on the differences in body image perceptions and satisfaction across the years of medical training. Objectives: The objective was to study the body image concerns and weight control behaviors among medical students in a private medical college in Oman and analyze differences among various groups of medical students (premedical, preclinical, and clinical). Materials and Methods: A cross-sectional study was conducted among students of a private medical college in Oman. Information regarding their body image perceptions, image satisfaction, and attempts to control weight was obtained through a self-administered questionnaire. Students' responses on self-reported body mass index (BMI), perceived body image, body image satisfaction, and weight control measures were collected, tabulated, analyzed, and interpreted. Results: A total of 351 medical students participated in the study (mean age of 21.56 ± 2.2 years, mean BMI of 22.7 ± 4.3 kg/m2, 87.7% females), of these 129 (36.8%), 112 (31.9%), and 110 (31.3%) students belonged to the premedical, preclinical, and clinical years, respectively. There were 226 (64.4%) students with normal BMI, 43 (12.3%) were underweight, and 82 (23.3%) overweight/obese. Incorrect image perceptions were observed in 204 (58.1%). One hundred and nine students (31.1%) were dissatisfied with their body image and 245 (69.5%) attempted to lose weight (earlier/currently). Perceived body image and body image satisfaction were significantly associated (P < 0.001); however, there was no association of body image perceptions/image dissatisfaction with self-reported BMI. Weight control measures such as exercise, calorie restriction, fasting, crash diet, and liquid diet were noted. Attempts to change weight were significantly related to students' perceived image (P < 0.001) and body image satisfaction (P = 0.011) but not to their self-reported BMI. No differences were found between students belonging to premedical, preclinical, and clinical years with respect to their body image perceptions, image satisfaction, BMI, attempts to change weight, and weight control methods (except fasting). Conclusions: Results indicate that body image misperceptions (58.1%) and image dissatisfaction (31.1%) exist among our medical students from Oman. Exposure to the knowledge of body image issues and eating disorders during their medical training did not positively impact their image perceptions/image satisfaction and weight control attempts across the years of study. This underlines the need to revise the medical curriculum through the introduction of awareness modules and psychoeducation sessions focusing on body image issues and healthy weight control behaviors.